2016
DOI: 10.1016/j.childyouth.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers' perspectives on parental health literacy and child health outcomes among Southeast Asian American immigrants and refugees

Abstract: Low health literacy has emerged as an important area of research because of its close link with health disparities. In this study, we used a qualitative approach to investigate healthcare providers' perspectives on the health literacy of immigrant and refugee parents and its association with children's health. Sixteen health and mental health professionals serving immigrant and refugee parents and children in various clinical settings were recruited through a purposive sampling method and interviewed. Six broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Also, it was noted that parents have a tendency to use alternative traditional remedies instead of medical prescriptions. 12 In the same fashion, in another study, physicians reported that refugees perceive depression as "sadness," which does not necessarily require formal treatment. 19 Mistrust is another issue connected to culture which manifests itself from the moment providers begin taking medical histories.…”
Section: Differences In Culture and Expectationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, it was noted that parents have a tendency to use alternative traditional remedies instead of medical prescriptions. 12 In the same fashion, in another study, physicians reported that refugees perceive depression as "sadness," which does not necessarily require formal treatment. 19 Mistrust is another issue connected to culture which manifests itself from the moment providers begin taking medical histories.…”
Section: Differences In Culture and Expectationsmentioning
confidence: 88%
“…10,11 In addition to the difficulties in taking proper medical history, the diagnosis of mental health problems is particularly a challenge because of the stigma about receiving treatment for mental health. 12 Differential understanding of health care due to cultural backgrounds is also a major challenge encountered by health care providers serving culturally diverse populations in day-to-day practice. In a study conducted in Alaska (USA) with Hmong refugees, it was observed that cross-cultural empathy is a key to proper service provision, and different beliefs of Hmong refugees towards health care should be responded through empathy.…”
Section: Differences In Culture and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…to be associated with greater prevalence of mental illness symptoms, [43][44][45] and poor parental health literacy predicted negative mental well-being for their children. 46 Furthermore, populations with low health literacy are less likely to seek professional help for mental illness symptoms 44,47 and…”
Section: Discussionmentioning
confidence: 99%
“…There is less evidence on how other forms of psychological distress (e.g., depression, anxiety, and pain) stemming from pre-and postmigration stressors as well as acculturation problems may influence parenting behavior on child psychosocial outcomes ( 6 ). A qualitative study of healthcare workers’ perceptions on parental health knowledge and child health effects among Southeast Asian American immigrants and refugees explored the following broad themes: complexity of parental health knowledge; experience from the respective home country and parent characteristics; the influence of the reception country system; help-seeking behavior from a culture point of view; and health symptoms on children ( 7 ). An interview study on the experiences of 17 Sudanese refugee women raising their teenagers in Australia, four main issues caught their main worries; such as the shift from child raising in an interdependent society as part of a network of family and community affairs (it takes a whole village to rear the child) to nurturing alone in the reception country context, mothers’ insecurity and practices of dropping their children, both literally and symbolically, defeat of parental authority, and the habits in mothers adjusted to the postmigration context and found new meaning of parenting ( 8 ).…”
Section: Introductionmentioning
confidence: 99%